Purple Urine Bag Syndrome: a Rare Manifestation of Urinary Tract Infection - Toyyibah, Ilma; Fajariya, Rosida; Keswardiono, Catur Budi; Lucas Teixeira Campos Queiroz; Tarissa Diandra Putri Wibowo (Indonesian Journal of Tropical and Infectious Disease, 2024)
Purple urine bag syndrome (PUBS) is rare manifestation of urinary tract infection (UTI). Epidemiological study showed the prevalence of purple urine bag syndrome about 8.3%-16.7% worldwide. There are some factors which lead to the disease including female, long-term urinary catheter, bedridden or immobile for long time, constipation, and urinary tract infection. The mechanism of this condition involves the tryptophan in intestine that is degraded into indole. In the liver, indole is conjugated into indoxyl sulphate. This conjugate product then is excreted into urine by the kidney. In the infected urinary tract, some  gram-negative bacteria produce enzymes called sulphatase and phosphatase. It converts the conjugated product, indoxyl sulphate into pigments, red indirubin and blue indigo. The two pigments-combination produces purple pigment which appears in urine. We present a-61-year-old female who has history of cerebrovascular accident who came to our emergency room with purple urine over the previous seven days.